Thalassonerita megastoma Moroni 1966 ... - Kiel, Steffen; Sami, Marco; Taviani, Marco (Zenodo, 2023)
Thalassonerita megastoma Moroni, 1966 Fig. 6A–B Nerita (Thalassonerita) megastoma Moroni, 1966: 71, pl. 1. Material examined ITALY – Emilia-Romagna • 5 specs; Caselle C; NRM Mo 204846. – Tuscany • 3 specs; Le Colline; MSF 1203 (W = 7 mm), MSF 1220 (H = 7.6 mm), MSF 1223 (W = 15.2 mm) • 6 specs; same collection data as for preceding; NRM Mo 204845. Remarks Thalassonerita megastoma has been reported and at times figured from various Calcari a Lucina sites of the Romagna Apennines (Moroni 1966; Taviani 1994, 1996, 2001, 2011; Sami & Taviani 2015, 2019; Kiel et al. 2023). Specimen MSF 1223 from Le Colline shows scars of the left and right columellar muscles, consistent with the anatomical sketch of the closely related extant species Thalassonerita naticoides (Clarke, 1989) provided by Warén & Bouchet (1993: fig. 2). Thalassonerita naticoides is a very common species at methane-seeps in the Gulf of Mexico and the Caribbean Sea (Clarke 1989; Warén & Bouchet 1993; Olu et al. 1997; Amon et al. 2017). ... : Published as part of Kiel, Steffen, Sami, Marco & Taviani, Marco, 2023, Mollusks (Gastropoda, Bivalvia) from Miocene cold-seep deposits in northern Italy: revisions and additions, pp. 115-160 in European Journal of Taxonomy 910 on pages 129-130, DOI: 10.5852/ejt.2023.910.2365, http://zenodo.org/record/10350702 ...